De Ritis ratio as a predictor of 1-year mortality after burn surgery. Issue 8 (December 2021) - Yu, Jihion; Kim, Hee Yeong; Kong, Yu-Gyeong; Park, Ji Hyun; Seo, Young Joo; Kim, Young-Kug
Highlights: This was the first study to assess the risk factors, including the De Ritis ratio, for 1-year mortality after burn surgery. The De Ritis ratio, defined as the aspartate aminotransferase to alanine aminotransferase ratio, was associated with 1-year mortality after burn surgery. The 1-year mortality rate after burn surgery was significantly higher in patients with a De Ritis ratio >1.9 than in those with a De Ritis ratio ≤1.9. These findings emphasized the importance of identifying burn patients with an increased De Ritis ratio to reduce the mortality after burn surgery. Abstract: Background: Burn is an overwhelming injury. The De Ritis ratio, defined as aspartate aminotransferase to alanine aminotransferase ratio, can be used to predict poor outcomes. We evaluated the risk factors, including the De Ritis ratio, associated with 1-year mortality after burn surgery. Methods: Patients who underwent burn surgery from 2009 to 2019 were retrospectively evaluated. Multivariate Cox regression analysis was conducted to evaluate the risk factors for 1-year mortality after burn surgery. Receiver operating characteristic (ROC) curve analysis of the De Ritis ratio was performed to predict postoperative 1-year mortality. Kaplan–Meier survival analysis was also conducted. Other postoperative outcomes, such as durations of hospital and intensive care unit stays, acute kidney injury, and major adverse cardiac events, were evaluated. Results: One-year mortality after burn surgery occurred in 247 (19.9%) of 1244 patients. The risk factors for 1-year mortality after burn surgery were the De Ritis ratio, age, American Society of Anesthesiologists physical status, diabetes mellitus, total body surface area burned, inhalation injury, serum creatinine level, and serum albumin level. The area under the ROC curve for the De Ritis ratio was 0.716 (optimal cutoff = 1.9). The 1-year mortality rate after burn surgery was significantly higher in patients with a De Ritis ratio >1.9 than in those with a De Ritis ratio ≤1.9 (35.8% vs. 11.8%, P  < 0.001). The survival rate was significantly higher in patients with a De Ritis ratio ≤1.9 than in those with a De Ritis ratio >1.9 (log-rank test, P  < 0.001). Intensive care unit stay, acute kidney injury, and major adverse cardiac events were significantly higher in patients with a De Ritis ratio >1.9 than in those with a De Ritis ratio ≤1.9 ( P  = 0.006, P  < 0.001, and P  < 0.001, respectively). Conclusions: The preoperative De Ritis ratio was a risk factor for 1-year mortality after burn surgery. The De Ritis ratio >1.9 was significantly associated with an increased 1-year mortality after burn surgery. These findings emphasized the importance of identifying burn patients with an increased De Ritis ratio to reduce the mortality after burn surgery.